Expenditure of developing a single educational space of multilevel innovative educational institutions - Kharkivska, Alla (My University, 2020)
The expediency of building a single educational space of multilevel innovative educational institutions is high-quality multi-level training of graduates who success-fully compete in the labor market, able to continuously improve their professional and universal knowledge, professional self-improvement throughout active life. To achieve this goal, training and education should be based on the paradigm of person-ally-oriented lifelong learning and the formation of humanistic views. The article highlights the key points of construction and implementation of the quality management process of continuing professional education in a single educa-tional space.
Kharkivska A. Expenditure of developing a single educational space of multilevel innovative educational institutions / A. Kharkivska // Danish Scientific Journal. – 2020. – №40. – Vol. 2. – Р. 42–46. (Переклад – Доцільність розбудови єдиного освітнього простору багаторівневих інноваційних закладів освіти)
Keywords: single educational space, multilevel innovative educational institu-tion, continuing education, management, performance quality.